The effects of prophylactic granisetron on maternal haemodynamics during elective caesarean section under spinal anaesthesia : a randomised control study - Ya'acob, Nurul Syuhada (2019)
Background: Neuraxial anaesthesia for caesarean delivery is preferred to general anaesthesia because it minimizes the risk of failed intubation, ventilation and aspiration. Maternal hypotension, a recognized complication of post spinal anaesthesia due to sympathetic blockage may be detrimental to the outcome due to pressure dependant uteroplacental flow. Granisetron, a selective 5-HT3 receptor antagonist potentially improves hypotension despite it usage as anti-emetic for post operative nausea and vomiting. The study conducted to determine the effects of prophylactic intravenous Granisetron on haemodynamics of parturients undergoing LSCS under SA as well as the usage of vasopressors intra-operatively. The Apgar score and post operative nausea and vomiting will be observed. Methods: This was a stratified balanced randomisation (1:1), single blinded, parallel group study conducted in Hospital Universiti Sains Malaysia. Eligible participants were screened preoperatively to meet the inclusion and exclusion criteria. Consented parturient scheduled for elective caesarean section under spinal anaesthesia were randomized into 2 arms, the group that received intravenous Granisetron pre spinal anaesthesia versus the group that received intravenous Granisetron 30 minutes post spinal anaesthesia using computerized software randomization. A slow bolus of intravenous Granisetron 1 mg was given. All patients were subjected to standard spinal anaesthesia using intrathecal heavy Marcaine 1.9mls (9.5mg) in combination with intrathecal morphine 0.1mg and intrathecal fentanyl 25mcg. Spinal anaesthesia is given at the level L3/L4 or L4/L5 using Pencan or Spinocan size 27G or 25G. All participants were placed on the operating table in the supine position, 15° of left lateral tilt with supplemental oxygen nasal prong 3 litres/min and standard haemodynamic monitoring, non-invasive blood pressure, SPO2, ECG and end tidal CO2. Haemodynamics and vasopressors requirement were recorded every 3 minutes for 30 minutes from the start of spinal anaesthesia. We used an analysis of variance (ANOVA) for the primary end point which studied mean arterial pressure and heart rate. The requirement of vasopressors was analysed using Chi-square test. The Apgar score and post operative vomiting were observed. Results: The results show that the mean MAP of parturients given intravenous granisetron pre spinal anaesthesia results was higher compare to the post spinal anaesthesia results for each time of measurements (p value < 0.05). There was no significant different between the two groups as for heart rate variation. The comparison between the 2 groups vasopressors ussage show significant difference (p<0.05), whereby the group that receives intravenous Granisetron prior of SA had stable hemodynamic and require less vasopressor compare to the other group. Both groups have no different in term of Apgar score and post operative nausea and vomiting. Conclusion: Intravenous Granisetron administration prior to spinal anaesthesia stabilize haemodynamic of parturients LSCS.